2014
DOI: 10.1016/j.hbrcj.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of coating layers used for thermal protection of FRP strengthened beams

Abstract: This paper investigates the efficiency of coating layers used for thermal protection of Fiber-Reinforced Polymer (FRP) strengthened Reinforced Concrete (RC) beams. An experimental program was carried out on 36 RC beams protected by using different coating layers of Perlite, Vermiculite, Portland Cement (PC) mortar, clay and ceramic fiber. The tested beams were exposed to 100, 200, 300, 400, 500, and 600°C for 2 h, left to cool gradually, then tested to failure. The obtained results demonstrated that exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Lu et al [8] concluded that with the increase in temperatures from ambient normal temperature up to 200 o C, the tensile strength and modulus of elasticity of BFRP plates were degraded by 37.5% and 31%, respectively. Limited studies are found in the literature to investigate the degradation level in the ultimate flexural capacity of FRP reinforced concrete beams [9][10][11][12][13][14][15][16][17][18]. Degradation level up to 19% in flexural capacity of GFRP reinforced concrete beams under 600 o C and up to 53% under 700 o C [9,10], where the authors reported that the temperature level measured at FRP bar level exceeded the critical temperature causing a rapid reduction in strength and stiffness of those beams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al [8] concluded that with the increase in temperatures from ambient normal temperature up to 200 o C, the tensile strength and modulus of elasticity of BFRP plates were degraded by 37.5% and 31%, respectively. Limited studies are found in the literature to investigate the degradation level in the ultimate flexural capacity of FRP reinforced concrete beams [9][10][11][12][13][14][15][16][17][18]. Degradation level up to 19% in flexural capacity of GFRP reinforced concrete beams under 600 o C and up to 53% under 700 o C [9,10], where the authors reported that the temperature level measured at FRP bar level exceeded the critical temperature causing a rapid reduction in strength and stiffness of those beams.…”
Section: Introductionmentioning
confidence: 99%
“…Using a thick insulation layer from calcium silicate boards, an ultra-thin coating system and PC embedded ceramic fiber blanket enabled the insulated beams to have a satisfactory fire endurance for two hours [11-13]. Kamal, et al [14] reported that a 50 mm thick PC embedded ceramic fiber blanket protected the insulated FRP strengthened beam and nearly preserved the flexural capacity to the same level as the control beam tested under ambient temperature. [15] tested BFRP-RC beams under elevated thermal exposure up to 925 °C for one hour.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that perlite-Portland cement and perlite-gypsum coatings are the most effective plasters as fire barriers and in retarding the conduction of high temperatures across their thickness among different kinds of coatings, such as traditional-cement plaster, vermiculite cement/gypsum-based mortar, intumescent coating, calcium silicate board, and LECA-cement plaster [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies were carried out for FPR-strengthened RC members under elevated temperatures or fire by several researchers [6][7][8][9][10]. To provide protection of carbon fiber reinforced polymer (CFRP) from direct fire exposure, a coating layer of a thermal insulating material, typically gypsum products, was placed around the beam cross-section [11,12]. A fire test program was conducted by Blontrock et al [6] in which ten CFRP-strengthened RC beams protected with calcium silicate boards were subjected to the design service loads of Eurocode [13].…”
Section: Introductionmentioning
confidence: 99%
“…Using a 50 mm thick layer of Perlite mortar has protected CFRP strengthening system against 500 o C for three hours with only 4 -12% loss in its capacity [11]. Different coating layers of Perlite, Vermiculite and Portland Cement mortars in addition to clay and ceramic fiber were studied and experimentally demonstrated to give protection and maintain 90% of the residual flexural capacity of FRP-strengthened beams compared to control beams after a two-hour exposure to 600 o C [12].…”
Section: Introductionmentioning
confidence: 99%